Capacidade de adesão, invasão e produção de enterotoxinas de Staphylococcus aureus isolados de leite de vacas com mastite subclínica e leite humano de um banco de leite - Zanutto, Mirella Rossitto [UNESP] (2015)
Staphylococcus aureus is one of the main pathogens involved in human and bovine mastitis. Among his many virulence factors is the ability to adhere and invade mammary epithelial cells, establishing the disease, produce enterotoxin that can cause foodborne poisoning, if any contaminated milk consumption. The objective of this study was to evaluate and compare the potential of adherence and invasion of S. aureus, isolated from dairy cows with subclinical mastitis and breast milk from a milk bank in culture bovine mammary epithelial cells (BMEC), HEp -2 and HeLa, searching genes involved in the formation of certain enterotoxins by PCR, verify the production of enterotoxins classical in vitro and investigate the presence of the mecA gene, which confers resistance to various beta lactam antibiotics. Were used 20 S. aureus isolates from milk cows with subclinical mastitis and 20 human milk from a milk bank of a public hospital in the city of Botucatu, SP. The isolated human milk showed better adhesion to HeLa cells (p = 0.043), while isolates from bovine milk adhered better to HEp-2 cells and BMEC (p = 0.01). In invasion testing, isolates from human milk and bovine invaded the three cell types indistinctly in percentage from 1 to 62.5% invasion for S. aureus of human origin and 0.7 to 100% for isolates from bovine origin. It was concluded that the adhesion test for human isolates can be used and HeLa cells isolated from bovine origin, can be used Hep-2 and BMEC cells. For testing invasion any cell type may be utilized for S. aureus from both origins. The gene encoding the enterotoxin C (sec) was the most common in both types of milk, with a prevalence of 90% (n = 18) and 80% (n = 16) in human and bovine, respectively. In human milk, sea was the most prevalent second, with 75% (n = 15), of which 11 (73.3%) produced SEA in vitro, followed sec, which was observed in 9 (45%) isolates of which 4 (44.5%) enterotoxin produced in vitro. The sea and ...